Ocorrência de fumonisinas em milho e derivados, destinados à alimentação humana - Oliveira, Dillaine Hennig de (2016)
The culture of corn is one of the most important segments for the economy of the Brazilian agriculture industry, being responsible for 37 % of the grains produced in the country. Therefore, due to its high nutritious value, it possesses a great vulnerability of fungus growth, especially for the Fusarium sp., which is a deteriorate agent and responsible for producing fumonisin, a group of mycotoxins of carcinogenic character and term stable, associated to outbreaks that reach to equine, suine and poultry and also lead to esophagus cancer in humans. Thus, the aim of this work was to evaluate the incidence of fumonisin in the corn and its derivatives during the industrialization process. A total of 1200 samples (300 maize, 300 of hominy, 300 of grits and 300 of corn flour) was collected among the processing of corn during May 2016 and submitted to fumonisin quantification by method of immunoassay ROSA® Fumonisin Quantitative Method. The detection limit was 250 µg/kg. In order to verify the existence of a Pearson correlation between two different methods for fumonisin quantification, other 23 samples (9 maize and 14 flour) were randomly collected in a parallel study, followed by fumonisin quantification by simultaneously ROSA® Fumonisin Quantitative Method and the Liquid Chromatography-Mass Spectrometry LC-MS/MS. Of the 1200 samples analyzed, 370 (30,83%) tested positive for total fumonisins with concentrations ranging 278-1.522 µg/kg in corn, 293-1.240 µg/kg in hominy, 269-445 µg/kg in grits and 267-512µg/kg in corn flour. However, fumonisin levels detected in corn and derivatives were lower than the maximum level established by Brazilian law, and therefore able for human consumption. The ROSA® method for fumonisin quantitation used in this work showed a strong positive Pearson correlation (r = 0.98) with the official method employed, indicating the possibility of its use in the quantification of mycotoxins by the processing industries, that require fast, reliable and cost-effective results. Despite the detected levels fumonisins did not represent any risks to the consumers health, the corn products monitoring there must be constant, seeing that the contamination through mycotoxins depends on a group of factors and represents a great challenge to the corn manufacturing industries.